2013
DOI: 10.1088/0954-3899/40/12/125202
|View full text |Cite
|
Sign up to set email alerts
|

Bag versus NJL models for colour–flavour-locked strange quark matter

Abstract: We compare the mass-radius relationship of strange stars obtained in two theoretical frameworks describing the colour-flavour-locking state of dense quark matter: the semi-empirical MIT bag model and a self-consistent approach using the Nambu-Jona-Lasinio (NJL) model. In the simplest MIT model extended to include pairing, one can make the equation of state stiffer by increasing the gap parameter so that larger maximum masses for these objects can be reached. In the NJL model, however, such an effect is not pos… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 33 publications
1
12
0
1
Order By: Relevance
“…When considering CFL matter through a Nambu-Jona-Lasinio (NJL) model with four-fermion interactions at finite density, other interactions, besides the diquark channel [37], can also be considered. Among these additional channels of interactions, vector interactions [38,39] are the most relevant as they can significantly affect the stiffness of the EOS, and hence they will be considered in our analysis.…”
Section: Modelling Of Self-bound Compact Starsmentioning
confidence: 99%
“…When considering CFL matter through a Nambu-Jona-Lasinio (NJL) model with four-fermion interactions at finite density, other interactions, besides the diquark channel [37], can also be considered. Among these additional channels of interactions, vector interactions [38,39] are the most relevant as they can significantly affect the stiffness of the EOS, and hence they will be considered in our analysis.…”
Section: Modelling Of Self-bound Compact Starsmentioning
confidence: 99%
“…8 in [15]). However, when other interactions, also present in a dense medium of quarks [42], such as the diquark channel [43] and/or the vector channel, were taken into account, the EOS stiffened enough to meet the 2M challenge. Because of these findings, quark matter was back in the competition as a possible core phase of massive stars (see for instance [44][45][46]).…”
Section: Inhomogeneous Quark Matter In the Core Of Compact Starsmentioning
confidence: 99%
“…It can be observed that the splitting between the EoS for different ∆'s is more significant for the values introduced in the MIT model than in those obtained in the NJL model, although they are really significant only for high gap values. As it was found in [18], in the MIT case, the higher the gap, the stiffer the EoS. Hence, as the mass supported by a given star configuration is related to the stiffness of the EoS, a higher value of the gap renders higher maximum masses for stable strange stars [8].…”
Section: Bag Vs Njl Model In the Cfl Phasementioning
confidence: 64%